Ingestion of microplastics by Hypanus guttatus stingrays in the Western Atlantic Ocean (Brazilian Amazon Coast). (January 2021) - Pegado, Tamyris; Brabo, Lucio; Schmid, Kurt; Sarti, Francesco; Gava, Thaís T.; Nunes, Jorge; Chelazzi, David; Cincinelli, Alessandra; Giarrizzo, Tommaso
Abstract: The present study documents, for the first time, the ingestion of microplastics (MPs) by Longnose stingrays in the Western Atlantic Ocean. We examined 23 specimens of Hypanus guttatus from the Brazilian Amazon coast and found microplastic particles in the stomach contents of almost a third of the individuals. Fibers were the most frequent item (82%), blue was the most frequent color (47%) and Polyethylene Terephthalate (PET) was the most frequent polymer recorded (35%), as identified by 2D imaging - Fourier Transform Infrared (FTIR). The ingestion of microplastics by Longnose stingray has not been previously recorded. The findings of the present study thus provide an important baseline for future studies of microplastic ingestion by dasyatid rays and other batoid species in the Atlantic Ocean, and contribute to the broader understanding of the spatial and temporal dimensions of the growing problem of plastic pollution in aquatic ecosystems and organisms. Highlights: MP particles were found in 30% of H. guttatus stomach contents. Fiber was the most frequent item found in H. guttatus stomach contents (82%). PET was the main polymer identified by 2D FTIR Imaging.